Methodological basics of system analysis of the current situation and problems in the Arctic zone of Russia - V. N. Leksin (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2015)
For the successful implementation of strategic documents on the development of the Russian Arctic region it is necessary to use modern technologies of system analysis of basic situations and problems in the functioning of the diverse territorial components in this zone. At the same time the methodology for working with arrays of mismatched information of Rosstat, ministries and agencies, major corporations acquires the particular importance.